2020
DOI: 10.1038/s41467-019-13892-x
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell analysis based dissection of clonality in myelofibrosis

Abstract: Cancer development is an evolutionary genomic process with parallels to Darwinian selection. It requires acquisition of multiple somatic mutations that collectively cause a malignant phenotype and continuous clonal evolution is often linked to tumor progression. Here, we show the clonal evolution structure in 15 myelofibrosis (MF) patients while receiving treatment with JAK inhibitors (mean follow-up 3.9 years). Whole-exome sequencing at multiple time points reveal acquisition of somatic mutations and copy num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 62 publications
3
56
0
Order By: Relevance
“…To date, FLT3 mutations are a widely recognized AML-associated driver mutations. The FLT3-TKD mutation, carried by the patient, like the canonical FLT3-ITD, constitutively activates the receptor and promotes cell proliferation16 .Regarding the global mutational profile of single cells studied at the zygosity level, we observed a significant increase in the clonal heterogeneity during disease evolution, in agreement with recent data by Mylonas et al17 . This causes the expansion of highly mutated clones in later stages of the disease, accounting for the worsening of the patient' conditions.…”
supporting
confidence: 91%
“…To date, FLT3 mutations are a widely recognized AML-associated driver mutations. The FLT3-TKD mutation, carried by the patient, like the canonical FLT3-ITD, constitutively activates the receptor and promotes cell proliferation16 .Regarding the global mutational profile of single cells studied at the zygosity level, we observed a significant increase in the clonal heterogeneity during disease evolution, in agreement with recent data by Mylonas et al17 . This causes the expansion of highly mutated clones in later stages of the disease, accounting for the worsening of the patient' conditions.…”
supporting
confidence: 91%
“… 28 , 29 Clonal evolution is not halted suggesting a rather limited disease-modifying potential. 30 , 31 …”
Section: Jak2 Inhibitors To Target Mpn Pathogenesismentioning
confidence: 99%
“…Clonal dynamics play a role as well, with higher JAK2 mutant allele fractions and lower number of mutations predicting favorable responses [ 22 , 23 ]. In addition, RAS pathway mutations have recently been associated with resistance to JAK inhibitors and poor outcomes [ 24 , 25 , 26 ]. Durability of spleen response to ruxolitinib treatment is associated with improved overall survival, while thrombocytopenia and clonal evolution correlate with inferior outcomes [ 27 , 28 ].…”
Section: Rationale For Combination Therapymentioning
confidence: 99%
“…Other combinations that are supported by preclinical data and have yet to reach, or just recently entered, clinical testing are worth noting. Recent reports have suggested that disease progression in MF patients treated with ruxolitinib is associated with activation of receptor tyrosine kinase and RAS pathway mutations, and RAS pathway mutations, including PTPN11 (which encodes the SHP2 phosphatase), confer poor prognosis [ 24 , 25 ]. Notably, inhibition of MEK, a mediator of MAP kinase signaling, has been shown to be effective in murine models as a single agent as well as in combination with ruxolitinib [ 175 ].…”
Section: Novel Combinations Pending Clinical Experiencementioning
confidence: 99%